The effectiveness of the Occupational Safety and Health Master Plan 2015 (OSH-MP 15) in enhancing government leadership and preventive workplace - Yaacob, Norhafizah; Mohd Tamrin, Shamsul Bahri; Ng, Yee Guan; How, Vivien; Ab Rahman, Rozanah; Zerguine, Haroun; Mohd Suadi Nata, Dayana Hazwani (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Background: Occupational Safety and Health Master Plan for Malaysia 2015 was intended to increase awareness, knowledge and commitment to Occupational Safety and Health in all undertaking to reduce the number of injuries, diseases and fatalities. Objectives: The purpose of this study is to determine the effectiveness of Occupational Safety Health Master Plan for Malaysia 2015 (OSH-MP 15) in enhancing government leadership and preventive workplace culture. Methods: This cross sectional study covered all the states in Malaysia, constituting of 309 employers, 350 Occupational Safety Health practitioners and 360 employees as respondents. There were three questionnaires for three different groups which were employers, Occupational Safety Health practitioners and general employees. The respondents were selected through random sampling. Results: For strategy 1, there was a significant difference in mean of effectiveness of OSH-MP15 between sectors for general workers [F (11, 348) =12.06, p=<0.001], OSH practitioners [F (11, 338) =1.19, p=0.033] and employers [F (11, 297) =5.62, p=<0.001]. For strategy 2, a significant difference in mean of effectiveness of OSH-MP15 between sectors was found for general workers [F (11, 348) =4.52, p=<0.001], OSH practitioners [F (11, 338) =2.28, p=0.011], employers [F (11, 297) =5.74, p=<0.001]. Conclusion: There was a significant difference between the effectiveness of fostering, and enhancing government leadership and inculcating preventive workplace culture among respondents. This study acts as the baseline data for the effectiveness of Occupational Safety and Health Master Plan 2015 in enhancing government leadership and preventive workplace culture.